Dual purpose barley (Hordeum vulgare L.) in India: Performance and potential - Kharub, Ajit Singh; Verma, Ramesh Pal Singh; Kumar, Dinesh; Kumar, Vishnu; Selvakumar, Rajan; Sharma, Indu (Journal of Cereal Research, 2013)
Barley for green forage and grain can be grown in semi arid and arid climatic conditions where no other green forage is available in winter months due to shortage of irrigation water or insufficient rains. New varieties have been developed zone wise for dual purpose barley and their performance has been evaluated in this study. The time of cut for green fodder was optimized and cutting 55 days after sowing was found optimum. A seed rate of 120 kg ha-1 and fertilizer dose of 75N:30P:20K kg ha-1 are optimum for dual purpose barley. Half of nitrogen and full P and K should be applied as basal and remaining half of nitrogen dose should be splited in two (half immediate after green fodder cut and half 30 days after cut). Irrigation immediately after forage cut is required for better rejuvenation. Barley grown with senji or mustard was equivalent with barley alone in producing green fodder and grain. Dual purpose barley provides nutrition rich green fodder for the livestock at the time of scarcity and at the same time also provides acceptable quality grain for human consumption. On an average, 180-240 and 24-35 q ha-1 of green fodder and grains, respectively were produced from dual purpose barley.